How the Financial Crisis Affects Pensions and Insurance and Why the Impacts Matter - Tower, Ian (IMF Working Papers; Working Paper ;, 2009)
This paper discusses the key sources of vulnerabilities for pension plans and insurance companies in light of the global financial crisis of 2008. It also discusses how these institutional investors transit shocks to the rest of the financial sector and economy. The crisis has re-ignited the policy debate on key issues such as: 1) the need for countercyclical funding and solvency rules; 2) the tradeoffs implied in marked based valuation rules; 3) the need to protect contributors towards retirement from excessive market volatility; 4) the need to strengthen group supervision for large complex financial institutions including insurance and pensions; and 5) the need to revisit the resolution and crisis management framework for insurance and pensions.